Apoptosis and reduced microvascular density of the lamina propria during tooth eruption in rats - Pizzol Júnior, José Paulo de; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (Anatomical Society., 2015)
During tooth eruption, structural and functional changes must occur in the lamina propria to establish the eruptive pathway. In this study, we evaluate the structural changes that occur during lamina propria degradation and focus these efforts on apoptosis and microvascular density. Fragments of maxilla containing the first molars from 9-, 11-, 13- and 16-day-old rats were fixed, decalcified and embedded in paraffin. The immunohistochemical detection of vascular endothelial growth factor (VEGF), caspase-3 and MAC387 (macrophage marker), and the TUNEL method were applied to the histological molar sections. The numerical density of TUNEL-positive cells and VEGF-positive blood vessel profiles were also obtained. Data were statistically evaluated using a one-way anova with the post-hoc Kruskal-Wallis or Tukey test and a significance level of P ≤ 0.05. Fragments of maxilla were embedded in Araldite for analysis under transmission electron microscopy (TEM). TUNEL-positive structures, fibroblasts with strongly basophilic nuclei and macrophages were observed in the lamina propria at all ages. Using TEM, we identified processes of fibroblasts or macrophages surrounding partially apoptotic cells. We found a high number of apoptotic cells in 11-, 13- and 16-day-old rats. We observed VEGF-positive blood vessel profiles at all ages, but a significant decrease in the numerical density was found in 13- and 16-day-old rats compared with 9-day-old rats. Therefore, the establishment of the eruptive pathway during the mucosal penetration stage depends on cell death by apoptosis, the phagocytic activity of fibroblasts and macrophages, and a decrease in the microvasculature due to vascular cell death. These data point to the importance of vascular rearrangement and vascular neoformation during tooth eruption and the development of oral mucosa.
Keywords: Apoptosis; Eruptive pathway; Lamina propria; Microvasculature; Tooth eruption